The effect of medium-term heat acclimation on endurance performance in a temperate environment - Corbett, J.; Massey, H. C.; Costello, J. T.; Tipton, M. J.; Neal, R. A. (European Journal of Sport Science, 2022)
We investigated whether an 11-day heat acclimation programme (HA) enhanced endurance performance in a temperate environment, and the mechanisms underpinning any ergogenic effect. Twenty-four males (VO2max: 56.7 ± 7.5 mL·kg-1·min-1) completed either: (i) HA consisting of 11 consecutive daily exercise sessions (60-90 min·day-1; n = 16) in a hot environment (40°C, 50% RH) or; (ii) duration and exertion matched exercise in cool conditions (CON; n = 8 [11°C, 60% RH]). Before and after each programme power at lactate threshold, mechanical efficiency, VO2max, peak power output (PPO) and work done during a 30-minute cycle trial (T30) were determined under temperate conditions (22°C, 50% RH). HA reduced resting (-0.34 ± 0.30°C) and exercising (-0.43 ± 0.30°C) rectal temperature, and increased whole-body sweating (+0.37 ± 0.31 L·hr-1) (all P=0.001), with no change in CON. Plasma volume increased in HA (10.1 ± 7.2%, P < 0.001) and CON (7.2 ± 6.3%, P = 0.015) with no between-groups difference, whereas exercise heart rate reduced in both groups, but to a greater extent in HA (-20 ± 11 b·min-1) than CON (-6 ± 4 b·min-1). VO2max, lactate threshold and mechanical efficiency were unaffected by HA. PPO increased in both groups (+14 ± 18W), but this was not related to alterations in any of the performance or thermal variables, and T30 performance was unchanged in either group (HA: Pre = 417 ± 90 vs. Post = 427 ± 83 kJ; CON: Pre = 418 ± 63 vs. Post = 423 ± 56 kJ). In conclusion, 11-days HA induces thermophysiological adaptations, but does not alter the key determinants of endurance performance. In trained males, the effect of HA on endurance performance in temperate conditions is no greater than that elicited by exertion and duration matched exercise training in cool conditions.